Rethinking White Societies in Southern Africa 1930s-1990s - Money, Duncan; van Zyl-Hermann, Danelle (Taylor & Francis, 2020)
This book showcases new research by emerging and established scholars on white workers and the white poor in Southern Africa. Rethinking White Societies in Southern Africa challenges the geographical and chronological limitations of existing scholarship by presenting case studies from Angola, Mozambique, South Africa, Zambia and Zimbabwe that track the fortunes of nonhegemonic whites during the era of white minority rule. Arguing against prevalent understandings of white society as uniformly wealthy or culturally homogeneous during this period, it demonstrates that social class remained a salient element throughout the twentieth century, how Southern Africa's white societies were often divided and riven with tension and how the resulting social, political and economic complexities animated white minority regimes in the region. Addressing themes such as the class-based disruption of racial norms and practices, state surveillance and interventions - and their failures - towards nonhegemonic whites, and the opportunities and limitations of physical and social mobility, the book mounts a forceful argument for the regional consideration of white societies in this historical context. Centrally, it extends the path-breaking insights emanating from scholarship on racialized class identities from North America to the African context to argue that race and class cannot be considered independently in Southern Africa. This book will be of interest to scholars and students of southern African studies, African history, and the history of race.